Strategic prospects of non-Olympic sports in Ukraine - Yaroslav Leonov; Galina Putiatina (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to identify strategic prospects for the development of non-Olympic sports in Ukraine. Materials and Methods: the analysis of literary sources and documents, systems analysis, organizational analysis, marketing tools, SWOT - analysis, organizational modeling, methods of mathematical statistics. 57 representatives of the regional federations of non-Olympic sports participated in the survey. Results: the model of sustainable development of non-Olympic sports is proposed. Objective necessity of the implementation of the results obtained in the practice to the state, branch and regional management in the sphere of physical culture and sports is proven. Conclusions: the livelihoods and development of non-Olympic sport involves the development and application of organizational projects, management of technology, "integrators" of local resources, the study of internal resource of sport movement, the development program funding.